Artificial intelligence in thrombosis: transformative potential and emerging challenges - Abdulrahman Al Raizah; Mshabab Alrizah (Thrombosis Journal)
Abstract Venous thromboembolism (VTE), including deep vein thrombosis (DVT) and pulmonary embolism (PE), continues to pose significant clinical challenges despite advancements in medical care. Artificial intelligence (AI) presents promising opportunities to enhance the diagnosis, prediction, and management of VTE. This review examines the transformative potential of AI in thrombosis care, highlighting both the potential benefits and the challenges that need to be addressed. Through an analysis of current applications and future directions, the review underscores AI’s role in advancing VTE management and improving clinical outcomes.